All climate stories worth telling. Salience and positionality at the intersection of news values and frames. (April 2019) - Moernaut, Renée; Mast, Jelle; Temmerman, Martina
Highlights: A combined framing-news values analysis allows for more profound insights. (Most) news values and subframes facilitate each other. The salience-enhancing devices of both methods complement and reinforce each other. The same visual-verbal conventions are used across ideological contexts. Subframes lay bare the various ideological views news values may help to convey. Abstract: The world is too complex for humans to grasp. Frames and news values (or 'journalistic selection procedures') make it more intelligible, foregrounding salient elements. Giving shape to reality, both concepts cannot be separated from ideological interests, either. Previous research suggests, accordingly, that frames and newsworthiness take shape in mutual interaction. Yet, the exact nature of this interaction remains unclear as in-depth discursive research is lacking. Therefore, we have conducted a combined framing-news value analysis, drawing on a corpus of climate articles published in three mainstream and two alternative media outlets in Northern Belgium. This article discusses the relations among four selected news values and the ideologically coloured subframes of the Cycles of Nature and Environmental Justice frames. The presented schemata and exemplary analyses demonstrate the strong overlap between the salience-enhancing devices of subframes and news values. Also, they make tangible the ideological argumentations at the intersection of newsworthiness and framing, explicating the diverging realizations of news values in the context of various subframes. As such, this study lays bare some of the journalistic conventions which are often used in climate reporting to naturalize certain worldviews. Moreover, it contributes to the development of the Discursive News Values Analysis framework proposed by (Bednarek and Caple (2017). The Discourse of News Values. How News Organizations Create Newsworthiness . New York, NY: Oxford UP).